Comparing Moral Hazard Behaviour of Micro and Small Enterprises on Productive Business Loan Repayment - Agus Arifin; FX. Sugiyanto; Wahyu Widodo (Media Ekonomi dan Manajemen, 2019)
This research aims to measure and compare the moral hazard behaviour of micro and small enterprises’ debtors within Purwokerto area on Productive Business Loan scheme. This scheme was choosen because of the highest Non Performing Loan (NPL) among others. The data were collected from 127 debitors by using simple random sampling technique. Rating scale method was used to measure the moral hazard behaviours of debtors through questionnaire and later comparing them to study how serious the noncompliance rate in repaying off their credits. This research finds that (1) Generally, the moral hazard behaviour tends to be medium-to-high, (2) The highest moral hazard should be attributed to debitors in Purbalingga followed by those in Banjarnegara, Purwokerto, and Cilacap. Then, it suggests that (1) all bank branches need to pay more attentions to their debitors because their moral hazard behaviours have been medium-to-high. (2) Each branch needs to apply specific treatments to the debitors to improve debitors’ installments, i.e building lending relationship as one way of exploring soft information which emphasizes informal approaches, (3) It should be important to design integrated training and practices for bank officers in order to build up their sense of psychological skills in public relationship in order to handle, in turn, those risky debtors.